Recent records, range loss, and current threats to the pampas deer Ozotoceros bezoarticus (Mammalia, Cervidae) in the state of Santa Catarina, Brazil - Rodrigo C. Benedet; Marcelo Mazzolli (Biotemas, 2009)
The native grasslands in the micro-region of Lages are the natural habitat of the pampas deer, and the locality of Coxilha Rica, known for its short grass, is its largest refuge in the state of Santa Catarina. Recent novel records of the pampas deer in this state are published here for the first time, as well as evidence of a reduction in its historical distribution. In a grassland environment that is increasingly invaded by plantations of exotic species, partition of land, and burning of grasslands, adequate management of the areas where the pampas deer still persist may be decisive for the survival of remaining populations.